Synthesis of Lipidated Peptides as Potential Therapeutics. - Rodenstein, Marissa Sharon. (Tufts Archival Research Center, 2016)
Part I:Glucagon-Like Peptide 2 (GLP-2) is a 33-amino acid hormone secreted upon nutrient ingestion by the enteroendocrine L cells of the gastrointestinal tract. GLP-2 binds to its cognate receptor (GLP-2R), leading to beneficial effects on the intestine by increasing blood flow and epithelial proliferation, improving nutrient absorption, and reducing inflammation of the intestinal mucosa. Although GLP-2 is degraded rapidly by the serine protease dipeptidyl peptidase 4 (DPP-4), a stable analog Gattex® (Teduglutide) has been developed for use in the treatment of Short Bowel Syndrome (SBS), a condition that results in inadequate absorption of nutrients through the bowel due to intestinal removal, disease, or injury. Teduglutide partially reduces the need for parenteral support (PS) for many patients with SBS. Therefore, a GLP-2R agonist with improved potency, durability, and stability was designed as a potential therapeutic for SBS and other intestinal ailments. By combining N-terminal protection to prevent DPP-4 cleavage and lipidation to allow interactions with blood albumin, a GLP-2 analog with extended longevity in the body and superior therapeutic potential was synthesized. Part II:The W-peptides (WKYMVM-NH2/WKYMVmNH2) are hexapeptide agonists of the formyl peptide receptor (FPR) family of G protein-coupled receptors (GPCRs). The FPRs act as checkpoints in host defense and can thus be exploited for anti-inflammatory drugs. WKYMVm-NH2 has improved potency compared to WKYMVM-NH2 but is not specific, acting as an agonist for both FPR1 and FPR2. To increase the potency of WKYMVM-NH2 while retaining its specificity for FPR2, the W-peptides were synthesized with lipid anchors. By increasing the local concentration of WKYMVM-NH2 at the membrane surface, a potent, specific FPR2 agonist was produced. This targeted therapeutic could be used as an anti-inflammatory agent, particularly to produce cardioprotective and anti-sepsis effects through FPR2 activation.